Immobilized strychnine as a new chiral stationary phase for HPLC - Sýkora, David; Vozka, Jiří; Tesařová, Eva; Kalíková, Květa; Havlík, Martin; Matějka, Pavel; Král, Vladimír (Electrophoresis, 2017)
A new ion-exchanger type chiral stationary phase for high-performance liquid chromatography was prepared. The synthetic protocol is based on derivatization of silica with (3-iodopropyl)trimethoxysilane in the first step followed by immobilization of strychnine via quaternization of nitrogen atom of the alkaloid strychnine. The synthesized chiral stationary phase was chromatographically characterized. The main effort was headed towards the evaluation of the enantioselectivity of the novel sorbent. For that purpose a set of suitable chiral probes, specifically, binaphthyl derivatives, was employed. The influence of methanol content, concentration of aqueous ammonium acetate buffer, and its pH on retention factors, separation selectivity, and resolution of the atropoisomers of the mentioned chiral solutes was studied in detail. It was demonstrated that the new chiral stationary phase was capable to separate atropoisomers of four out of seven testing compounds. Despite the strong influence of the above mentioned variables on retention, their impact on selectivity and resolution was rather moderate. Concerning retention mechanism, it seems that electrostatic interaction between the positively charged quaternary nitrogen of the chiral stationary phase and anionic solute participates significantly in the retention process.
Keywords: Chiral stationary phase; Methanol; Binaphthyl derivatives; stereoizomerie; Acetates; Chromatography, High Pressure Liquid; Chiral separation; strychnin; Alkaloid; Stereoisomerism; acetáty; vysokoúčinná kapalinová chromatografie; Strychnine; methanol